The effect of self-monitoring the INR on quality of anticoagulation and quality of life - Kulinna, Wolfgang; Ney, Dietrich; Wenzel, Thomas; Heene, Dieter L.; Harenberg, Job (Seminars in thrombosis and hemostasis, 1999)
Thieme E-Books & E-Journals
Elektronische Reproduktion der Druck-Ausgabe 06. Februar 2008
Gesehen am 18.05.2022